2001
DOI: 10.1128/jvi.75.14.6710-6713.2001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cells Are Highly Susceptible to Human Immunodeficiency Virus Type 1 Infection and Release Infectious Virus

Abstract: Plasmacytoid dendritic cells (pcDC) and myeloid dendritic cells (myDC) are shown to express CD4 and low levels of CCR5 and CXCR4, but only myDC express DC SIGN, a C-type lectin that binds human immunodeficiency virus but does not mediate virus entry. Both DC types were more susceptible to infection with a macrophage than a lymphotropic strain of human immunodeficiency virus type 1, but pcDC were more readily infected than myDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(148 citation statements)
references
References 11 publications
5
140
1
1
Order By: Relevance
“…Contrasting what we observed in the blood where there were more PDCs in PBMCs from SHIVinfected monkeys (17), the percentages of PDCs were comparable in LNCs from naive and SHIV-infected animals. HIV reportedly infects blood-derived PDCs, increasing cell viability (83,84), and this may be what we have observed in the blood but not LNs of the SHIV-infected animals. Whether this reflects inherent differences between PDCs in the blood and lymphoid tissues and/or differences in the distribution of DC subsets between blood and tissues needs to be elucidated.…”
Section: Discussionsupporting
confidence: 53%
“…Contrasting what we observed in the blood where there were more PDCs in PBMCs from SHIVinfected monkeys (17), the percentages of PDCs were comparable in LNCs from naive and SHIV-infected animals. HIV reportedly infects blood-derived PDCs, increasing cell viability (83,84), and this may be what we have observed in the blood but not LNs of the SHIV-infected animals. Whether this reflects inherent differences between PDCs in the blood and lymphoid tissues and/or differences in the distribution of DC subsets between blood and tissues needs to be elucidated.…”
Section: Discussionsupporting
confidence: 53%
“…35 Both myeloid and plasmacytoid DC subsets were infectable with HIV-1 in vitro when high amounts of HIV-1 were used, through CD4 and the chemokine receptors CCR5 and CXCR4. 20,36 However, here we show that CD4 ϩ blood DC were not able to transmit HIV-1 virus to T lymphocytes at low concentrations of virus, as opposed to DC-SIGN ϩ blood DCs, which potently captured and transmitted low amounts of HIV-1 to T cells through DC-SIGN. It is possible that capture of HIV by DC-SIGN ϩ blood DCs could be responsible for the infection of other blood DC subsets or T cells in blood.…”
Section: Discussionmentioning
confidence: 63%
“…However, recent studies demonstrated that myeloid and lymphoid precursor DC subsets in blood lack DC-SIGN expression. 20,21 We set out to investigate the expression of DC-SIGN by human blood mononuclear cells. Initial experiments showed the presence of a small population of cells (0.02% of total PBMCs) that expressed DC-SIGN and that could be visualized by direct staining in human blood ( Figure 1A).…”
Section: Isolation and Characterization Of Dc-sign-expressing Cells Imentioning
confidence: 99%
See 1 more Smart Citation
“…The destruction of HIV-specific naive CD4 T cells may occur following their recruitment into infected lymphoid sites, where they may be killed directly after their specific priming and infection by HIV-infected dendritic cells. 123,124 Accordingly, during acute infection, rapidly proliferating HIV-specific memory CD4 þ T cells are highly susceptible to HIV infection, and they were found to contain more HIV viral DNA than other memory CD4 þ T cells, 123 indicating their preferential infection in vivo and consequently their preferential loss. Langherans cells are likely initial targets for HIV following sexual exposure to virus and, following their infection, they were shown to preferentially transmit HIV to proliferating autologous memory CD4 þ T cells, further dying of apoptosis after antigenic stimulation.…”
Section: How Apoptosis Impairs Hiv-specific Immunity Destruction Of Hmentioning
confidence: 99%